Indoor Air Particulates in Broiler Environment During Winter - Ahmed, Zakia A.M.; Ghamdi, Zahraa H.EL; Al-Namshaan, Mashael M. (International Journal of Poultry Science, 2011)
The impact of winter climate on indoor and outdoor air particulate concentrations (ID and ODPC), concentrations of TSP, sizes and nature in broiler houses were recorded weekly. In closed and Open houses (Chs and OHs) significant positive correlations were recorded between ID and OD climate. Significantly decreased ID Ta.oC and A.V m/sec and increased RH% in open vs closed. OD Ta.oC significantly decreased and RH% increased around OHs vs CHs. In CHs increased (OPC) vs (IPC) except at the 3rd and 4th week. The Indoor Organic Particulate (IOP) started small in sizes (1-2 μm ID and < 5 μm OD). The maximum Particulate Concentration (PC) and sizes were at 3rd week old age on floor litter. In OHs the IPC were permanently increased vs OPC except at the 1st week. Before chicks admission (IOP) were dominated. The Chemical Composition of Organic Particulate Ones (CCOP) showed higher SIO % vs Inorganic Particulate (IP). The indoor organic and inorganic particulates (IOP and IIP) were of big sizes and contained variable percents of non organic oxides of Si+4, AL+3 and Ca+2. IP was smaller than OP at early age but increased with age and contained variable percents of SI, Fe and Ca oxides. Conclusively the dominancy of IOP and OOP with large sizes before admission to 3rd week may induce health risk for birds and keepers. Improper controlled system in stocked poultry houses and the outdoor climate positively affected the indoor one especially in winter.